Physical Properties and H i-to-H2 Transition across Taurus Linear Edge - Ningyu Tang; Feihang Miao; Gan Luo; Di Li; Junzhi Wang; Fujun Du; Donghong Wu; Shu Liu (The Astrophysical Journal)
Studying the atomic-to-molecular transition is essential for understanding the evolution of the interstellar medium. The linear edge of the Taurus molecular cloud, clearly identified in the ^13 CO(1–0) intensity map, serves as an ideal site for investigating this transition. Utilizing the Arizona Radio Observatory Submillimeter Telescope, we obtained mapping observations of CO(2–1), ^13 CO(2–1), and CO(3–2) across this linear edge. The intensity ratio between CO(2–1) and ^13 CO(2–1) indicates a lower limit of the ^12 C / ^13 C ratio of 54 ± 17. Based on multitransition observations of CO and ^13 CO, we performed a Markov Chain Monte Carlo fit of the physical properties across this edge using non–local thermodynamic equilibrium analysis with the RADEX code, based on the large velocity gradient assumption. The number density profile exhibits a pronounced jump coinciding with the H _2 infrared emission peak. The cold H i gas within the molecular cloud, manifested as H i narrow self-absorption features, is detected along the cloud edge. Our quantitative comparison with numerical simulations provides tentative evidence that shocks induced by colliding gas flows may contribute to the atomic-to-molecular phase transition observed along the linear edge.